Analisis Dampak Abu Vulkanik Erupsi Gunung Lewotobi Laki-Laki terhadap Produktivitas Tanaman Mete di Desa Tou Barat, Kabupaten Ende - Tuti Asmiranti Sina; Vinsensia Mayestica Sefrin; Rana Nurwidhad Aprina; Sulasmi Sulasmi; Yeremias Bardi (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the impact of volcanic ash from the eruption of Mount Lewotobi Laki-laki on the productivity of cashew plants in Tou Barat Village, Ende Regency. The study is based on the high dependence of the village community on cashew crops as a primary source of income, meaning environmental disturbances such as volcanic ash have the potential to reduce their welfare. The research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation, with research subjects including cashew farmes, village officials, agricultural extension workers, and community leaders. The results indicate that volcanic ash has physical impscts in the form of leaf and flower drop, a decline in fruit quality, and a reduction in productivity by 30-50%. Chemical impacts were also identified throught changes in soil fertility due to acidification, with soil pH dropping to below 5.0. although farmers have tried to adapt, such as through manual clearing and adding organic fertilizers, the results have not been optimal. The implications of this study emphasize the impotance of government and related institutions’ support in providing mitigation facilities, disaster adaptation training, and resilient plantation management policies against volcanic risks.